2020
DOI: 10.1093/mollus/eyaa013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hybrid Pyganodon grandis and P. lacustris (Bivalvia: Unionidae) using F- and M-type mitochondrial DNA sequences and geometric morphometrics

Abstract: Pyganodon grandis and P. lacustris, widespread and common species in North America, are known to co-occur across parts of their distributions. These mussels are genetically distinguishable with a sequence divergence between 9% and 13% for the mitochondrial (mt) DNA barcoding region, cytochrome c oxidase subunit I (COI), which is well beyond thresholds for distinct species. The objectives of this study were to (1) confirm the presence of two genetically distinct species (P. grandis and P. lacustris) in Font Lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…However, counter examples do exist. For instance, Beauchamp et al (2020) found more F-type haplotypes than M-type haplotypes in Pyganodon grandis (11 and 7, respectively) and P. lacustris (20 and 6, respectively). Smietanka et al 2013 (87 F- and 76 M-type haplotypes in Mytilus trossulus ) and Riginos et al 2004 (132 F- and 56 M-type haplotypes in Mytilus edulis ) reported the same pattern, although the latter results might be due to the difficulty of amplifying the male-type mtDNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, counter examples do exist. For instance, Beauchamp et al (2020) found more F-type haplotypes than M-type haplotypes in Pyganodon grandis (11 and 7, respectively) and P. lacustris (20 and 6, respectively). Smietanka et al 2013 (87 F- and 76 M-type haplotypes in Mytilus trossulus ) and Riginos et al 2004 (132 F- and 56 M-type haplotypes in Mytilus edulis ) reported the same pattern, although the latter results might be due to the difficulty of amplifying the male-type mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Most hypotheses on the role of selection, mutation and effective population size in shaping genetic diversity in DUI bivalves remain to be empirically tested.However, counter examples do exist. For instance,Beauchamp et al (2020) found more F-type haplotypes than M-type haplotypes in Pyganodon grandis (11 and 7, respectively) and P. lacustris (20 and 6, respectively).Smietanka et al 2013 (87 F-and 76 M- type haplotypes in Mytilus trossulus) andRiginos et al 2004 (132 F-and 56 M-type…”
mentioning
confidence: 95%
“…Morphometric analysis has also advanced considerably over the last 30 years with the development of landmark-based morphometric analyses making the quantification of shapes much more rigorous and reliable [15]. Modern morphometric analyses, in combination with DNA barcoding, has the potential to greatly clarify and quantify differences between morphologically problematic and difficult to identify species; these techniques have been applied to freshwater mussels and have proven useful for aiding in identifying morphologically difficult species [16][17][18][19] and near-microscopic juvenile mussels [13].…”
Section: Introductionmentioning
confidence: 99%
“…Los análisis de morfometría geométrica fueron ampliamente utilizados en unionoideos (Bailey & Green, 1988;Beauchamp et al, 2020;Beyett etal., 2020;Cano-Otalvaro et al, 2012;Echem et al, 2016;Fassatoui et al, 2015;Inoue et al, 2014;Jeratthitikul et al, 2019;Keogh et al, 2019;Morais et al, 2014;Troncon & Avelar, 2011;Zieritz & Alridge, 2009Zieritz et al, 2010). Autores como Baker et al (2003Baker et al ( , 2004…”
Section: Antecedentes En Unionoideosunclassified
“…La información taxonómica precisa sobre los unionoideos cobra vital importancia en términos de conservación, como ya se explicó en la sección 1.4. La morfometría geométrica es un método que ha sido utilizado en unionoideos (Bailey & Green, 1988;Beauchamp et al, 2020;Beyett etal., 2020;Cano-Otalvaro et al, 2012;Echem et al, 2016;Fassatoui et al, 2015;Inoue et al, 2014;Jeratthitikul et al, 2019;Keogh et al, 2019;Morais et al, 2014;Troncon & Avelar, 2011;Zieritz & Alridge, 2009Zieritz et al, 2010). Si bien se probó su capacidad para distinguir especies cercanas, esta herramienta no ha sido aún utilizada para resolver las discrepancias taxonómicas dentro del género Diplodon.…”
Section: Introductionunclassified